Eco-friendly and Enantiospecific Biginelli Synthesis Using (+)-Myrtenal as the Substrate – An Impeccable and Unequivocal Analysis of the Product - Dias Benincá, Luiza A.; Pereira Ligiéro, Carolina Bastos; da Silva Santos, Jonas; Junior, Joel Jones; da Silva, Flavia Martins (Current Organic Synthesis, 2020)
Background: We found in the literature, an excellent review of the Biginelli reaction that addresses the methodologies for obtaining enantiopure dihydropyrimidinones (DHPMs). In 1992, optically pure DHPMs were obtained by fractional crystallization of the diastereomeric ammonium salt derivative with (S)-(-) and (R)- (+)-α-methyl benzylamine and by other chiral resolution techniques, such as chiral high-performance liquid chromatography (HPLC). Asymmetric syntheses of these compounds are also explained in the literature. The main strategy is to use acid catalysts such as organophosphates, organometallic complexes, amines and diamines, nanocomposites, and chiral ionic liquids, e.g., L-prolinium sulfate (Pro2SO4). Objective: The objective was to study the Biginelli reaction with a chiral aldehyde. Methods: A mixture of ethyl acetoacetate (0.26 g, 3 mmol), urea (0.18 g, 3 mmol) and ethyl lactate (EL) (1 mL) was left under heating at 70°C and stirring for 1 h. Next, (-)-(1R)-myrtenal (0.45 g, 3 mmol) was added, and the medium was heated for 5 h more until the formation of a white solid. Ten millilitres of distilled water was added, and the product was extracted with CH2Cl2 (3 x 4 mL). The solvent was evaporated, and the product was recrystallized from ethanol-water. Results and Discussion: (+)-Myrtenal was used as a chiral substrate for a study that led to ethyl (R)-4-((1R,5S)- 6,6-dimethylbicyclo [3.1.1]hept-2-en-2-yl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate by the Biginelli synthesis using EL as a green solvent. The result is the first example of the enantiospecific Biginelli reaction. The product was exhaustively characterized by several physical analysis methods, i.e., 1H, 13C and 2D nuclear magnetic resonance (NMR) spectroscopies, infrared (IR) spectroscopy, mass spectrometry (MS), and high-resolution MS (HRMS), and its structure was unequivocally elucidated by X-ray crystallography. Conclusion: Compound (4R)-4-(6,6-dimethylbicyclo[3.1.1]hept-2-en-2-yl)-6-methyl-2-oxo-1,2,3,4- tetrahydropyrimidine- 5-ethyl carboxylate is the first example of the enantiospecific Biginelli reaction. In addition, the process has the advantage of using EL as a green solvent. The product was characterized by 1H, 13C, and 2D NMR and IR spectroscopy, MS, HRMS, and X-ray crystallography.
Keywords: myrtenal